MISKONSEPSI MAHASISWA TENTANG EFEK FOTO LISTRIK - Hamdani Hamdani (Universitas Tanjungpura, 2020)
AbstractThis research was conducted to reveal students' misconceptions about the photoelectric effect. There were 58 students (13 male and 45 female) who answered 12 diagnostic test questions in the form of multiple-choice with open reasons. Misconceptions revealed include the order in which the colors of the rainbow disrupt photon energy; light intensity is affected by frequency; electron emission will occur when the light intensity and frequency of light are changed even though the frequency of the light used is smaller than the cutoff frequency. Male and female students have the same opportunity to misconceptions.Keywords: Misconception, Photoelectric Effect, Gender